The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/gt.2010.152
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-expressing human umbilical cord mesenchymal stem cells, an improved therapy strategy for Parkinson’s disease

Abstract: The umbilical cord provides a rich source of primitive mesenchymal stem cells (human umbilical cord mesenchymal stem cells (HUMSCs)), which have the potential for transplantation-based treatments of Parkinson's Disease (PD). Our pervious study indicated that adenovirus-associated virus-mediated intrastriatal delivery of human vascular endothelial growth factor 165 (VEGF 165) conferred molecular protection to the dopaminergic system. As both VEGF and HUMSCs displayed limited neuroprotection, in this study we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 42 publications
1
66
0
1
Order By: Relevance
“…Several reports have demonstrated neuroprotection after experimental hUC-MSC xenotransplantation with or without immunosuppressive treatment, and there is no consensus as to the need for immunosuppression for optimal neuroprotection. Some studies have shown the survival of numerous transplanted cells for periods as long as 4 mo, even though no immunosuppression was used (6,59,97). Contrarily, in similar animal models, few transplanted cells could be identified a few weeks after transplantation in immunosuppressed animals (98).…”
Section: Potential Shortcomings Of the Use Of Huc-mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have demonstrated neuroprotection after experimental hUC-MSC xenotransplantation with or without immunosuppressive treatment, and there is no consensus as to the need for immunosuppression for optimal neuroprotection. Some studies have shown the survival of numerous transplanted cells for periods as long as 4 mo, even though no immunosuppression was used (6,59,97). Contrarily, in similar animal models, few transplanted cells could be identified a few weeks after transplantation in immunosuppressed animals (98).…”
Section: Potential Shortcomings Of the Use Of Huc-mscsmentioning
confidence: 99%
“…Xiong et al engineered hUC-MSCs to make them express GFP and vascular endothelial growth factor. They injected these cells into the rotenone-lesioned striatum of hemiparkinsonian rats, and observed an improvement in apomorphine-induced rotational behavior (97). It should be noted that despite the absence of immunosuppression, no immunological rejection was observed and many transplanted cells survived up to 12 wk after transplantation.…”
Section: Effect Of Huc-mscs In Adult Preclinical Models Of Neurologicmentioning
confidence: 99%
“…Both human and rat UCMSC also possess a strong tropism to various tumor tissues [32,33] and other inflammatory lesions [17,34,35]. Both human and rat UCMSC were specifically localized in the periphery of the tumor tissues when they were transplanted ( Fig.…”
Section: Ucmsc Home To Tumor Tissuesmentioning
confidence: 99%
“…For example, Yang et al have shown that transplantation of human UCMSC into the lesion site of a spinal cord injury is beneficial to wound healing in rats [16]. Parkinson`s disease is a potential target for the UCMSC therapy since transplanted UCMSC can be differentiated into dopaminergic neuron-like cells [17]. In addition, Chao et al, have reported that human UCMSC can be differentiated into mature islet-like cell clusters, and they possess an insulin-producing ability and significantly alleviated diabetic conditions in rats [18].…”
Section: Potential Application Of Ucmsc For Various Diseasesmentioning
confidence: 99%
“…Based on the structure and function, neurotrophic factors (NTFs) are divided into several families: (1) nerve growth factor (NGF)-superfamily, including nerve growth factor (NGF), brain derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), neurotrophin -4/5 (NT-4/5) and neurotrophin-6 (NT-6); (2) glial cell line-derived neurotrophic factor (GDNF) family, including glial cell line derived neurotrophic factor (GDNF), neurturin (NTN) and persephin (PSP); (3) neurokine superfamily, including ciliary neurotrophic factor (CNTF), leukemia inhibitory factor (LIF), interleukin (IL) and cardiotrophin (CT); (4) non-neuronal growth factor-superfamily, including some members of fibroblast growth factor superfamily, epidermal growth factor (EGF) [10], insulin-like growth factor (IGF) [11,14], bone morphogenetic protein (BMP) [2,8,12]. Furthermore, other growth factors also have neurotrophic function, such as vascular endothelial growth factor (VEGF) and erythropoietin (EPO) [34,35]. Most of these neurotrophic factors are protein or glycoprotein and are suitable to prepare sustained release microspheres [22,31,[36][37][38][39].…”
Section: Notesmentioning
confidence: 99%